PENINGKATAN USAHA PENGEPUL BARANG BEKAS DI KOTA SURABAYA - Abdul Halik; Dony Perdana; M. Adhi Prasnowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
The volume of waste and limited land to disposal accompanied and highpopulation growth, where this statement also by the technical wastemanagement still conventional. Waste management urban especially inresidential areas until now generally is done through the stage of activity asfollows, namely: packing the garbage, collecting garbage from the houses toLPS (disposal depot), transferring garbage directly to LPA (Final DisposalSite) or from LPS ( Temporary Disposal Site) to LPA, until the waste isdisposed in LPA. Shortly, garbage from urban area contains 10 % (weight)material that can be recycled ( paper, iron, cans, etc ), 50 % of them is organicmatter and 40 % of residue. Then, 60 % ( weight) dump can be recycled: 10 %can be reused, and 50 % can be composited ( anonymous, 1992 ). The datafrom Surabaya’s Sanitary Agency mentions that the total of daily volume ofgarbage in Surabaya is 79,19 % that all of them form the household. Integratedwaste management systems need to combine reduction the waste, recycling &reusing, compositing, the incinerating and final disposal. Reduction source ofgarbage for industry need zero-waste technology and simple/minimal packingproducts that has environmentally friendly. While, the habitual of wastefulshould be left for the households .Then, the approach recycling and reusingapplied particularly to the non-organic like paper, plastic, aluminum, glass,metal and others. A lack of awareness of waste and the level of publicconsumption and other activities make the waste kept piled up in the finaldisposal site ( LPA) . Waste commonly found in the landfill among other bottlesbeverages , detergents , and plastic bags .The waste the less attractive makes usreluctant to see an even a glance at. In fact if we want to try, the waste canbecome business opportunities. Even if we want to manage it properly, thisbusiness could be the power source. Most cans is made of aluminum through aprocess that require a lot of energy. Garbage cans recyclable with melt andmade aluminum as a starter new products .Thus, can additional energy sources,pollution can be reduced , and resources bauxite , lime and sodium carbonateas a starter aluminum can be efficient.Keywords: waste, recycling , flat, and incomes.